Descending projection neurons in the primary sensorimotor cortex regulate neuropathic pain and locomotion in mice - Guo-Hong Wang; Xin-Yu Hou; Hui-Zhu Liu; Zi-Rui Zhou; Su-Su Lv; Lan-Xing Yi; Hui Li; Yu-Qiu Zhang (Nature Communications)
Abstract Cortical descending modulation of sensory processing in the spinal cord has been revealed, the role of cortico-brainstem projections in sensory and motor regulation remains poorly investigated. Here, we identified two previously unappreciated subpopulations in the primary sensorimotor cortex (SM1), which are anatomically and electrophysiologically distinct but functionally similar, projecting to the periaqueductal gray (PAG) and rostroventral medulla (RVM), respectively. Postsynaptic PAG glutamatergic neurons then project to the noradrenergic (NA) neurons in the locus coeruleus (LC) and 5-HT neurons in the RVM to drive spinal NA and 5-HT anti-nociception, while RVM enkephalinergic neurons that receive SM1 projections directly drive spinal opioid analgesia. Intriguingly, silencing these two SM1 subpopulations impair motor behaviors and motor-induced analgesia, but does not affect behavioral responses to cutaneous sensory stimuli. Our findings indicate that these brainstem-projecting SM1 subpopulations are crucial for cortical descending pain modulation, which could be exploited to optimize pain relief approaches.